Coal char gasification for co-production of fuel gas and methane decomposition catalysts. (5th April 2022) - Yang, Wencheng; Zhang, Jianbo; Zhang, Lei; Li, Jingying; Bai, Yonghui; Yan, Ze; Ma, Xiaoxun; Hou, Cuili; Yao, Wengui
Abstract: Partial gasification of coal char was conducted with addition of metal oxides for co-production of fuel gas and methane decomposition catalysts. Effect of the metal composition (Ni, Co and Fe based mono- or bi-metals) was investigated on the fuel gas production and the resultant catalyst surface and textural properties, morphology and performance in catalytic methane decomposition (CMD). Besides H2 -rich fuel gas production (the combustion energy up to 11.03–23.42 MJ/kgchar ) from the gasification, the gasification residue can directly serve as the effective and efficient catalyst for CMD. The Fe and Fe–Co composite oxides were found to be better among the mono- and bi-metallic oxides for the fuel gas production during the gasification, respectively. The Ni-based mono-/bi-metallic catalysts could display high and stable methane conversion (up to 80%) during the 600-min CMD test at 850 °C. Promotional role of the second metal in CMD was discussed on the carbon diffusion, metal mobility and reducibility, formation and growth of the deposited carbons. The formed carbon morphology after CMD was analyzed based on the Kirkendall effect and Tammann temperature and further correlated to the potential catalyst deactivation. Graphical abstract: Image 1 Highlights: Partial gasification of coal char (<39%) is studied with addition of metal oxides. Co-production of H2 -rich (>60%) fuel gas and CH4 pyrolysis catalysts are achieved. Effects of Ni, Co and Fe mono-/bi-metals are studied at the content of about 10%. Kirkendall effect and Tammann temperature are used to analyze the formed carbons.